Utilization of chicken manure as organic fertilizer to increase growth and production Elephant grass (Pennisetum purpureum) - Gomera Bouk; Maria Kristina Sinabang (Journal of Tropical Animal Science and Technology, 2023)
This study aims to determine the level of growth and production of Pennisetum purpureum which is given organic fertilizer based on chicken manure with different proportions. This research was carried out on land belonging to the Independent Farmers group in Leosama village, Kakuluk Mesak sub-district, Belu Regency, East Nusa Tenggara, which started from March to June 2022. This research was carried out using the experimental method with a Randomized Block Design (RDB) consisting of 4 treatments and 4 replications so that there are 16 experimental plots in total. The treatments tested consisted of: K) Control (without chicken manure); PA) Pennisetum purpureum is given organic fertilizer made from 25% chicken manure; PB) Pennisetum purpureum is given organic fertilizer made from 50% chicken manure; and PC) Pennisetum purpureum fertilized with organic fertilizer made from 75% chicken manure. The results showed that the application of organic fertilizers made from chicken manure had a very significant effect (p<0.01) on the growth of plant height, number of leaves and leaf length as well as the fresh weight and dry weight of Pennisetum purpureum plants. The conclusion of this study is the use of organic fertilizers made from chicken manure up to 75% is the best in increasing the growth and production of Pennisetum